The Impact Of Unemployment, Minimum Wage, And Education On Economic Growth In Regencies/Cities In Bali Province - Christin Anastasya Melati Br Nainggolan; Made Kembar Sri Budhi (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Economic growth in Bali Province is predominantly driven by the tourism, service, and agricultural sectors, which play a vital role in the region’s development and income generation. Over the 2014–2024 period, however, the province has experienced a fluctuating and generally declining growth trend, influenced by both internal and external economic dynamics. This study aims to examine the influence of unemployment, district minimum wage (Upah Minimum Kabupaten/Kota—UMK), and education on economic growth across the nine regencies and cities in Bali Province. Employing a quantitative approach with an associative research design, the study utilizes panel data that combines cross-section data (9 regencies/cities) and time-series data spanning 2014–2024, yielding a total of 99 observations. To ensure robust estimation, panel data regression analysis was conducted, with the Random Effect Model (REM) selected as the most appropriate method based on the results of the Hausman test. The empirical findings reveal that, simultaneously, unemployment, UMK, and education have a significant influence on regional economic growth in Bali. Partially, education exerts a positive and significant effect, indicating that improvements in educational attainment and quality can drive higher productivity and foster sustainable economic development. Conversely, UMK demonstrates a negative and significant impact, suggesting that increases in the minimum wage, while beneficial for workers’ welfare, may impose financial burdens on businesses—particularly small and medium-sized enterprises—thus potentially slowing economic activity. Similarly, unemployment has a negative and significant effect, underscoring its detrimental role in limiting economic output and household income. These results emphasize the need for policymakers to strike a balance between enhancing workforce welfare through wage regulations and ensuring that such measures do not hinder economic competitiveness. Furthermore, strengthening education policies, improving access to quality learning, and aligning educational outcomes with labor market demands are crucial for supporting long-term economic growth in Bali.